UNIVERSITY STUDENTS’ STRATEGIES IN EXPLORING IDEAS OF PRE-WRITING ACTIVITIES IN WRITING CLASS - Kamal Yusuf; Agustin Dwi Trisiana (Universitas Sarjanawiyata Tamansiswa, 2020)
This study investigates university students’ strategies in pre-writing activity, what students usually do to explore their idea before writing an academic paper. The participants of this study were students of writing class majoring English Education Department at UIN Sunan Ampel Surabaya. An exploratory mixed methods design was employed by interviewing students in writing class about the strategy they used before writing and administering questionnaire respondents. The findings showed that students used several strategies to enrich the idea before writing, most students used draft on the essay, and the draft was used to collect the idea so that they could arrange their writing into a good structure. This implies the need for future research to investigate more about the strategy they use not only in pre-writing but also the used strategy to solve their problem in a writing activity.